2023
DOI: 10.1007/jhep09(2023)200
|View full text |Cite
|
Sign up to set email alerts
|

The connection between nonzero density and spontaneous symmetry breaking for interacting scalars

Alberto Nicolis,
Alessandro Podo,
Luca Santoni

Abstract: We consider U(1)-symmetric scalar quantum field theories at zero temperature. At nonzero charge densities, the ground state of these systems is usually assumed to be a superfluid phase, in which the global symmetry is spontaneously broken along with Lorentz boosts and time translations. We show that, in d > 2 spacetime dimensions, this expectation is always realized at one loop for arbitrary non-derivative interactions, confirming that the physically distinct phenomena of nonzero charge density and spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…Although we will not prove in full generality that the U(1) V symmetry is unbroken at finite density, we will provide evidence that the system can support a finite density phase with unbroken symmetry. This should be contrasted with the result discussed in [1] for the O(N ) vector model, where we showed that, for a system of N scalars, the breaking of the U(1) symmetry is instead inevitable at nonzero charge density, in the large-N limit.…”
Section: Jhep02(2024)182contrasting
confidence: 99%
See 4 more Smart Citations
“…Although we will not prove in full generality that the U(1) V symmetry is unbroken at finite density, we will provide evidence that the system can support a finite density phase with unbroken symmetry. This should be contrasted with the result discussed in [1] for the O(N ) vector model, where we showed that, for a system of N scalars, the breaking of the U(1) symmetry is instead inevitable at nonzero charge density, in the large-N limit.…”
Section: Jhep02(2024)182contrasting
confidence: 99%
“…In the presence of interactions, the fate of the internal U(1) symmetry in a state of finite charge density is less clear. For systems of interacting scalar fields, in [1] we have provided evidence that the ground state at finite chemical potential cannot develop a charge density unless it spontaneously breaks the U(1) symmetry (see also [2,3] for previous related discussions). We have proven this statement in perturbation theory at one loop for generic non-derivative scalar's self-interactions, and in a O(N ) vector model at large N .…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations